Low-Dose Crizotinib, a Tyrosine Kinase Inhibitor, Highly and Specifically Sensitizes P-Glycoprotein-Overexpressing Chemoresistant Cancer Cells Through Induction of Late Apoptosis in vivo and in vitro - Kim, Kyeong Seok; Jiang, Chunxue; Kim, Ji Young; Park, Jae Hyeon; Kim, Hae Ri; Lee, Su Hyun; Kim, Hyung Sik; Yoon, Sungpil (Frontiers in Oncology, 2020)
We investigated possible conditions or drugs that could target P-glycoprotein (P-gp)-overexpressing drug-resistant KBV20C cancer cells. Specifically, we focused on identifying a single treatment with a relatively low half maximal inhibitory concentration (IC50). Our approach utilized repurposing drugs, which are already used in clinical practice. We evaluated thirteen TKIs (gefitinib, imatinib, erlotinib, nilotinib, pazopanib, masatinib, sunitinib, sorafenib, regorafenib, lapatinib, vandetanib, cediranib, and crizotinib) for their sensitizing effects on P-gp-overexpressing drug-resistant KBV20C cells. We found that crizotinib had a much greater sensitization effect than the other tested drugs at relatively low doses. In a detailed quantitative analysis using both lower doses and time-duration treatments, we demonstrated that crizotinib, which increased the levels of apoptosis and G2 arrest, was the best TKI to induce sensitization in P-gp-overexpressing KBV20C cells. Upon comparing resistant KBV20C cells and sensitive KB parent cells, crizotinib was found to markedly sensitize drug-resistant KBV20C cancer cells compared with other TKIs. This suggests that crizotinib is a resistant cancer cell-sensitizing drug that induces apoptosis. In mice bearing xenografted P-gp-overexpressing KBV20C cells, we confirmed that crizotinib significantly reduced tumor growth and weight, without apparent side effects. In addition, although lapatinib and crizotinib have a high P-gp inhibitory activity, we found that co-treatment with crizotinib and vincristine (VIC) did not have much of a sensitization effect on KBV20C cells, whereas lapatinib had a high sensitization effect on VIC-treated KBV20C cells. This suggests that crizotinib is a single-treatment specific drug for resistant cancer cells. These findings provide valuable information regarding the sensitization of drug-resistant cells and indicate that low-dose crizotinib monotherapy may be used in patients with specific P-gp-overexpressing chemoresistant cancer.